Modeling of Digital and it Development in EU Countries - Полозова, Т. В.; Шейко, І. А.; Рижий, В. М. (ХНУРЕ, 2023)
Digital transformation is one of the priorities of future development in EU. Existance of EU Digital single market allow members to coordinate their effors in digitalization and support cooperation and trade.
Keywords: digital transformation; IT development; digitization; European countries